Inovasi Video Tutorial Tari Semarang Rumah Kita sebagai Media Pembelajaran Tari Siswa Kelas VIII di SMP N 7 Semarang - Aulia Azka Septyana; Lesa Paranti (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Dance instruction in schools still does not fully support students' ability to understand techniques and movement sequences independently. In the "Semarang Rumah Kita" dance material in grade VIII of SMP N 7 Semarang, the learning process tends to rely on classical methods guided by printed books. This condition indicates the need to develop more varied, interesting, and effective learning media. This study aims to develop and test the feasibility and effectiveness of the "Semarang Rumah Kita" dance video tutorial as a learning medium. The method used is Research and Development (R&D) which includes the stages of needs analysis, product planning, revision, and field trials. The research subjects were grade VIII students of SMP N 7 Semarang. Data were obtained through interviews, observations, validation questionnaires from material experts and media experts, and assessment of student practice. The data were analyzed using quantitative and qualitative descriptive approaches. The results of the study indicate that the developed video tutorial meets the criteria of very feasible and has been proven effective in increasing movement accuracy, cohesiveness, and student self-confidence. These findings are an innovative alternative to support dance learning and improve the quality of dance education in schools.